p53-dependent chromatin relaxation is required for DNA double-strand break repair - Chen Hongyu; Shan Jin; Qi Wenjing; Chen Lili; Zeng Xianlu (Acta Biochimica et Biophysica Sinica)
The tumor suppressor p53, an indispensable nuclear transcription factor, plays a central role in orchestrating cellular responses when DNA damage occurs. In this study, we demonstrate that in the initial phases of DNA double-strand break (DSB) repair, p53 is rapidly recruited to sites of damage and the surrounding chromatin, where it enhances DSB repair efficiency. This enhancement occurs through the modulation of chromatin dynamics and the promotion of a more relaxed chromatin configuration, a process influenced by p53 in response to DSB-inducing factors such as etoposide, ultraviolet radiation, and nucleases. These results underscore the pivotal function of p53 <?A3B2 tlsb=-.015w?>as a rapid responder to DSBs, delineating a significant departure from its traditionally recognized role as a downstream <?A3B2 tlsb?> transcriptional regulator in DNA damage repair processes. This study emphasizes that the direct engagement of p53 in DNA repair through chromatin structure regulation extends beyond its established involvement in UV irradiation-induced nucleotide excision repair (NER), demonstrating analogous mechanistic attributes in the context of DSB repair. This newly illuminated perspective enhances our understanding of the multifaceted roles of p53 in genome stability and integrity.